Anti-inflammatory Activity of Camellia sinensis, l. Extract Cream Combined with Vitamin C as Antioxidant on Croton Oil-induced Inflamation in Male Mice Strain BALB/C - Nining Sugihartini; Ratih Saridewi; Ulfa Ramdhani M; Fitri Rahmawanti; Sapto Yuliani; Vivi Sophia (Majalah Obat Tradisional, 2017)
Green tea extract cream contains epigallocatechin gallate (EGCG) as the active ingredient for anti-inflammatory. Epigallocatechin gallate is easyly oxidized and able to reduce its effectivity as an anti-inflammatory. Therefore, an addition of antioxidants in order to increase its stability is required. The purpose of this study was to determine the effect of adding the antioxidant Vitamin C on the effectivity of green tea extract as an anti-inflammatory. This study uses 6 groups of male mice strain BALB/C which were given treatment as follows: normal control, negative control, base cream, green tea extract (0.2%), Vitamin C cream (1%) and green tea extract cream with addition of Vitamin C. The anti-inflammatory activity was evaluated based on the expression of COX-2, inflammatory cells and the thickness of the epidermis in the skin tissue of mice after given crotton oil (0.1%) on the back for the induction of inflammation. After treatment cream for 3 days, mice were sacrificed for histopathological tissue preparations made with hematoxylin eosin staining and immunohistochemistry COX-2. Data were analyzed statistically with one way Anova followed by t-test to determine differences between groups at a significance level of 0.05. The test results indicate that cream of green tea extract is higher in decreasing inflammatory parameters in comparison with cream of Vitamin C, except in the thickness of epidermal parameter. Green tea extract cream with the addition of Vitamin C is higher in reducing inflammatory parameters than cream of green tea extract or cream of Vitamin C. The decline percentage of cells that express COX-2, inflammatory cells and the thickness of the epidermis in the each of groups were cream of green tea extract:57.95%;53.75%;34.83%, cream of Vitamin C:48.76%;34.96%;34.27%, cream of green tea extract and Vitamin C:61,89%;65,54%;46.30%, respectively. Based on the results of this study, it can be concluded that anti-inflammatory activity of green tea extract cream increased due to the addition of 1% vitamin C as an antioxidant.